2010
DOI: 10.1002/adma.201000746
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes in the Biological Interphase: The Relevance of Noncovalence

Abstract: With the increasing interest in the biological applications of carbon nanotubes, their interactions in the biological interphase and their general cytotoxicity have become major issues. In spite of their salient properties, major hurdles still exist for their use in biological applications, due to their main characteristics, including their hydrophobic surfaces and tendency to aggregate, as well as their unknown interactions in the cellular interphase. In this Research News, these characteristics of carbon nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 63 publications
1
61
0
1
Order By: Relevance
“…[59,60] Fluorescence imaging studies on fluorescent carbon nanotubes have thus far focused primarily on the measurement of the steady state spatial changes in emission intensity or wavelength. [4,[15][16][17][18][19]21,23,[61][62][63][64][65][66][67][68] The use of fluorescence lifetime imaging microscopy (FLIM) in combination with multiphoton excitation and near infrared (NIR) femtosecond laser pulses is widely used in the study of small molecule fluorophores particularly for in vitro studies. [69][70][71][72] To date FLIM has been used primarily on endogenous molecules such as tryptophan and common fluorescent dyes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[59,60] Fluorescence imaging studies on fluorescent carbon nanotubes have thus far focused primarily on the measurement of the steady state spatial changes in emission intensity or wavelength. [4,[15][16][17][18][19]21,23,[61][62][63][64][65][66][67][68] The use of fluorescence lifetime imaging microscopy (FLIM) in combination with multiphoton excitation and near infrared (NIR) femtosecond laser pulses is widely used in the study of small molecule fluorophores particularly for in vitro studies. [69][70][71][72] To date FLIM has been used primarily on endogenous molecules such as tryptophan and common fluorescent dyes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…56 A number of reviews have discussed CNT functionalization with many different organic groups and with more detailed information. [57][58][59] The dimensions of the CNT become especially relevant to conduct studies on a nanoscale, since its size simulates collagen protein at the nanoscale level. One of the features already fully understood from the ECM is the necessity to submit your manuscript | www.dovepress.com have in its physical structure a substrate that can interact with fibrous protein, maintaining its integrity for a long time (retarding proteolysis).…”
Section: Required Characteristics For a Desirable Scaffold And Its Immentioning
confidence: 99%
“…In fact, one study looked at the cellular uptake of several types of functionalized SWCNTs and found that cellular internalization is independent of the functional groups or cell type, which confi rms their potential use as a drug-delivery vehicle (Kostarelos et al ., 2007). Although CNT internalization methods are not well identifi ed, researchers have described two main pathways of passive diffusion through the lipid bilayers of cell membrane and energy-dependent endocytosis (Madani et al ., 2011;Lee and Geckeler, 2010). It has been observed that the short SWCNTs (≤400 nm) are generally transported to the nucleus, as shown in Fig.…”
Section: Drug and Factor Deliverymentioning
confidence: 92%